Disease-Specific Target Gene Expression Profiling of Molecular Imaging Probes: Database Development and Clinical Validation - Lawrence Wing-Chi Chan; Connie Hiu-Ching Ngo; Fengfeng Wang; Moss Y. Zhao; Mengying Zhao; Helen Ka-Wai Law; Sze Chuen Cesar Wong; Benjamin Yat-Ming Yung (Molecular Imaging, 2014)
Molecular imaging probes can target abnormal gene expression patterns in patients and allow early diagnosis of disease. For selecting a suitable imaging probe, the current Molecular Imaging and Contrast Agent Database (MICAD) provides descriptive and qualitative information on imaging probe characteristics and properties. However, MICAD does not support linkage with the expression profiles of target genes. The proposed Disease-specific Imaging Probe Profiling (DIPP) database quantitatively archives and presents the gene expression profiles of targets across different diseases, anatomic regions, and subcellular locations, providing an objective reference for selecting imaging probes. The DIPP database was validated with a clinical positron emission tomography (PET) study on lung cancer and an in vitro study on neuroendocrine cancer. The retrieved records show that choline kinase beta and glucose transporters were positively and significantly associated with lung cancer among the targets of 11 C-choline and [ 18 F]fluoro-2- deoxy-2-D-glucose (FDG), respectively. Their significant overexpressions corresponded to the findings that the uptake rate of FDG increased with tumor size but that of 11 C-choline remained constant. Validated with the in vitro study, the expression profiles of disease-associated targets can indicate the eligibility of patients for clinical trials of the treatment probe. A Web search tool of the DIPP database is available at http://www.polyu.edu.hk/bmi/dipp/ .